Exercise-based cardiac rehabilitation in patients with reduced left ventricular ejection fraction: The Cardiac Rehabilitation Outcome Study in Heart Failure (CROS-HF): A systematic review and meta-analysis. (June 2020) - Bjarnason-Wehrens, Birna; Nebel, R; Jensen, K; Hackbusch, M; Grilli, M; Gielen, S; Schwaab, B; Rauch, B; ,
Background: In heart failure with reduced left ventricular ejection fraction (HFrEF) patients the effects of exercise-based cardiac rehabilitation on top of state-of-the-art pharmacological and device therapy on mortality, hospitalization, exercise capacity and quality-of-life are not well established. Design: The design of this study involved a structured review and meta-analysis. Methods: Evaluation of randomised controlled trials of exercise-based cardiac rehabilitation in HFrEF-patients with left ventricular ejection fraction ≤40% of any aetiology with a follow-up of ≥6 months published in 1999 or later. Results: Out of 12, 229 abstracts, 25 randomised controlled trials including 4481 HFrEF-patients were included in the final evaluation. Heterogeneity in study population, study design and exercise-based cardiac rehabilitation-intervention was evident. No significant difference in the effect of exercise-based cardiac rehabilitation on mortality compared to control-group was found (hazard ratio 0.75, 95% confidence interval 0.39–1.41, four studies; 12-months follow-up: relative risk 1.29, 95% confidence interval 0.66–2.49, eight studies; six-months follow-up: relative risk 0.91, 95% confidence interval 0.26–3.16, seven studies). In addition there was no significant difference between the groups with respect to 'hospitalization-for-any-reason' (12-months follow-up: relative risk 0.79, 95% confidence interval 0.41–1.53, four studies), or 'hospitalization-due-to-heart-failure' (12-months follow-up: relative risk 0.59, 95% confidence interval 0.12–2.91, four studies; six-months follow-up: relative risk 0.84, 95% confidence interval 0.07–9.71, three studies). All studies show improvement of exercise capacity. Participation in exercise-based cardiac rehabilitation significantly improved quality-of-life as evaluated with the Kansas City Cardiomyopathy Questionnaire: (six-months follow-up: mean difference 1.94, 95% confidence interval 0.35–3.56, two studies), but no significant results emerged for quality-of-life measured by the Minnesota Living with Heart Failure Questionnaire (nine-months or more follow-up: mean difference –4.19, 95% confidence interval –10.51–2.12, seven studies; six-months follow-up: mean difference –5.97, 95% confidence interval –16.17–4.23, four studies). Conclusion: No association between exercise-based cardiac rehabilitation and mortality or hospitalisation could be observed in HFrEF patients but exercise-based cardiac rehabilitation is likely to improve exercise capacity and quality of life.